2017
DOI: 10.1001/jamaoncol.2017.0029
|View full text |Cite
|
Sign up to set email alerts
|

Birth Outcomes Among Adolescent and Young Adult Cancer Survivors

Abstract: Live births to AYA cancer survivors may have an increased risk of preterm birth and low birth weight, suggesting that additional surveillance of pregnancies in this population is warranted. Our findings may inform the reproductive counseling of female AYA cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
100
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 23 publications
10
100
1
3
Order By: Relevance
“…As in previous studies, we found survivors to have a significantly increased risk for preterm delivery compared to comparison subjects. We also found a 45% higher risk for overall hospitalization among survivors compared to population comparisons but could not identify any specific reasons for the increased risk for hospitalization as most survivors belonged to the category hospitalization for other reasons than vaginal bleeding, pre‐eclampsia or threatened preterm labor.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As in previous studies, we found survivors to have a significantly increased risk for preterm delivery compared to comparison subjects. We also found a 45% higher risk for overall hospitalization among survivors compared to population comparisons but could not identify any specific reasons for the increased risk for hospitalization as most survivors belonged to the category hospitalization for other reasons than vaginal bleeding, pre‐eclampsia or threatened preterm labor.…”
Section: Discussionsupporting
confidence: 87%
“…Various explanations for this elevated risk have been offered. Abdomino‐pelvic irradiation and chemotherapy have been identified as risk factors for preterm delivery and low birth weight of the fetus . In these survivors, the cancer treatment could lead to impaired uterine growth and reduced blood flow, resulting in uterine fibrosis and cervical shortening.…”
Section: Introductionmentioning
confidence: 99%
“…Previous U.S.‐based studies have suggested that low birth weight and preterm deliveries are more common among breast cancer survivors relative to the general population . However, among women who conceive after diagnosis, the magnitude of these associations appears to be modest.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies from Canada and Europe have documented a decreased incidence of childbirth among breast cancer survivors relative to age‐matched women in the general population. Other reports suggest that those who do give birth after breast cancer may have an increased risk of low birth weight and preterm deliveries compared to women without cancer . However, variation in these outcomes according to factors such as hormone receptor status and endocrine therapy use has not been previously explored.…”
Section: Introductionmentioning
confidence: 99%
“…29 Some studies have reported associations between stress during pregnancy and preterm delivery, 30 low delivery weight, 31 When stratifying by publication year, the association between breast cancer history and the risks of preterm delivery and low delivery weight appeared to be slightly stronger in studies published before 2010 compared with those published after 2010. 29 Some studies have reported associations between stress during pregnancy and preterm delivery, 30 low delivery weight, 31 When stratifying by publication year, the association between breast cancer history and the risks of preterm delivery and low delivery weight appeared to be slightly stronger in studies published before 2010 compared with those published after 2010.…”
Section: Discussionmentioning
confidence: 99%